Parthenolide Is Neuroprotective in Rat Experimental Stroke Model: Downregulating NF-κB, Phospho-p38MAPK, and Caspase-1 and Ameliorating BBB Permeability - Lipeng Dong; Huimin Qiao; Xiangjian Zhang; Xiaolin Zhang; Chaohui Wang; Lina Wang; Lili Cui; Jingru Zhao; Yinxue Xing; Yanhua Li; Zongjie Liu; Chunhua Zhu (Mediators of Inflammation)
Inflammatory damage plays an important role in cerebral ischemic pathogenesis and may represent a target for treatment. Parthenolide (PN) has been proved to elicit a wide range of biological activities through its anti-inflammatory action in the treatment of migraine, arthritis, and atherosclerosis. To decide whether this effect applies to ischemic injury in brain, we therefore investigate the potential neuroprotective role of PN and the underlying mechanisms. Male Sprague-Dawley rats were randomly divided into Saline, Vehicle, and PN groups and a permanent middle cerebral artery occlusion (MCAO) model was used. PN administered intraperitoneally immediately after cerebral ischemia and once daily on the following days. At time points after MCAO, neurological deficit, infarct volume, and brain water content were measured. Immunohistochemistry, western blot and RT-PCR were used to analyze the expression of NF-κB and caspase-1 in ischemic brain tissue. Phospho-p38MAPK and claudin-5 were detected by western blot. The results indicated that PN dramatically ameliorated neurological deficit, brain water content, and infarct volume, downregulated NF-κB, phospho-p38MAPK, and caspase-1 expressions, and upregulated claudin-5 expression in ischemic brain tissue. Conclusions. PN protected the brain from damage caused by MCAO; this effect may be through downregulating NF-κB, phosho-p38MAPK, and caspase-1 expressions and ameliorating BBB permeability.